GAMBARAN STATUS KEBERSIHAN RONGGA MULUT DAN KESEHATAN JARINGAN PERIODONTAL PADA IBU HAMIL DI WILAYAH PERKEBUNAN GLANTANGAN, KABUPATEN JEMBER - Prastifa, Febi Zulaikha; Sari, Desi Sandra; Praharani, Depi (Jurnal Kesehatan, 2024)
Introduction: During pregnancy, there are changes in hormone levels that can affect the condition of the oral cavity. An increase in hormones leads to gingival changes and a decrease in salivary flow that can affect the hygiene of the oral cavity and periodontal tissues leading to the occurrence of local inflammation and increased plaque accumulation. A sustained increase in plaque accumulation leads to periodontal disease. The purpose of this study was to determine the hygiene status of the oral cavity and the health of the periodontal tissue of pregnant women. Method: This type of research is descriptive observational with a total sampling data collection technique involving 51 pregnant women in 8 posyandu Pondokrejo Village, Glantangan Plantation area. Data collection was obtained through the oral hygiene index simplified (OHI-S), Community Periodontal Index of Treatment Needs (CPITN), and questionnaires. Results: The results of the OHI-S examination of pregnant women were obtained at 58.8% including moderate criteria, 35.3% bad, and 5.9% good. CPITN results are healthy periodontal 0%; bleeding when probing 0%; calculus and other retentive factors 86.3%; pathological pocket 4-5 mm 11.8%; pathological pocket 6 mm 2%. Pregnant women were most in the age of 26-35 years (58.82%), 3rd trimester (41.18%), last primary education (43.14%), had one-sided chewing habits (56.86%), never visited the dentist (92.16%), never scaling (90.20%), and brushed their teeth every bath (68.63%). Conclusion: The most common oral health status in pregnant women in the glantangan plantation area is moderate. The most common periodontal tissue health status in pregnant women is the condition that it is supragingival or subgingival calculus or there are debris retentive factors such as crowns and restorations that are not adapted properly.